2008
DOI: 10.1108/15982688200800008
|View full text |Cite
|
Sign up to set email alerts
|

A Study of General Reducing Criteria of Customer‐Oriented Perceived Gap for Hotel Service Quality

Abstract: In recent years, speedy development of Taiwan’s hotel industry intensifies market competition, customers’ demands on hotel services quality also increase with the increase of their consumption consciousness, and their demands on hotel types diversify, therefore hotel industry should concern on their unique management services quality brought by their different hotel types. The current designed service system or service transmission process may fail to meet customers’ demands owing to emphasizing degree gap in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Moreover, Gajewska et al [13] argued that customer satisfaction is the key to companies' competitiveness and can be considered the essence of success in today's highly competitive world of business. Chen et al [14], in their study of developing an electronic commerce user-consumer satisfaction index, included factors that were relating to both service encounters and service processes. Moreover, Naeem [15] showed that on-line stores must provide adequate post-sales services to support the customers' needs in the entire buying process.…”
Section: E-satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Gajewska et al [13] argued that customer satisfaction is the key to companies' competitiveness and can be considered the essence of success in today's highly competitive world of business. Chen et al [14], in their study of developing an electronic commerce user-consumer satisfaction index, included factors that were relating to both service encounters and service processes. Moreover, Naeem [15] showed that on-line stores must provide adequate post-sales services to support the customers' needs in the entire buying process.…”
Section: E-satisfactionmentioning
confidence: 99%
“…In comparing the SEM models, we followed the procedures outlined by Anderson and Gerbing [14]. According to [15], the comparison of the models is determined by calculating the difference in x 2 values.…”
Section: Model Comparison Of Vietnam With Taiwanmentioning
confidence: 99%
See 1 more Smart Citation